Analysis Study and Research on Heart Attack Prediction System - Singh, Harkirat; Gupta, Shivam; Chopra, Vinay (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 10 No 1&2 (2023): Journal of Advanced Research in Instrumentation and Control Engineering, 2023)
Abstract A blood clot disrupts blood flow to the heart, causing a heart attack. This may cause chest tightness, fullness, squeezing, or discomfort. This discomfort may spread. The study uses machine learning to predict heart attacks. A big dataset of heart attack survivors and non-survivors trained and tested the algorithm. The algorithm calculates a patient’s risk of a heart attack based on age, blood pressure, cholesterol levels, and other factors. Logistic regression, random forests, and support vector machines are machine learning methods. Finally, the novel heart attack prediction method may increase early diagnosis and prevention.   How to cite this article: Singh H, Gupta S, Chopra V. Analysis Study and Research on Heart Attack Prediction System. J Adv Res Instru Control Engi. 2023; 10(1): 5-9.